The transcription factor PstSTE12 is required for virulence of Puccinia striiformis f. sp. tritici. (25th September 2017) - Zhu, Xiaoguo; Liu, Wei; Chu, Xiuling; Sun, Qixiong; Tan, Chenglong; Yang, Qian; Jiao, Min; Guo, Jun; Kang, Zhensheng
Summary: Puccinia striiformis f. sp. tritici ( Pst ) is an obligate biotrophic fungus that causes extensive damage in wheat. The pathogen is now known to be a heteroecious fungus with an intricate life cycle containing sexual and asexual stages. Orthologues of the STE12 transcription factor that regulate mating and filamentation in Saccharomyces cerevisiae, as well as virulence in other fungi, have been extensively described. Because reliable transformation and gene disruption methods are lacking for Pst, knowledge about the function of its STE12 orthologue is limited. In this study, we identified a putative orthologue of STE12 from Pst in haustoria‐enriched transcripts and designated it as PstSTE12 . The gene encodes a protein of 879 amino acids containing three helices in the homeodomain, conserved phenylalanine and tryptophan sites, and two C2 /H2 ‐Zn 2+ finger domains. Real‐time reverse transcription‐polymerase chain reaction (RT‐PCR) analyses revealed that the expression of PstSTE12 was highly induced during the early infection stages and peaked during haustorium formation and the pycniospore stage in the aecial host barberry. Subcellular localization assays indicated that PstSTE12 is localized in the nucleus and functions as a transcriptional activator. Yeast one‐hybrid assays revealed that PstSTE12 exhibits transcriptional activity, and that its C‐terminus is necessary for the activation of transcription. PstSTE12 complemented the mating defect in an α ste12 mutant of S .  cerevisiae . In addition, it partially complemented the defects of the Magnaporthe oryzae mst12 mutant in plant infection. Knocking down PstSTE12 via host‐induced gene silencing (HIGS) mediated by Barley stripe mosaic virus (BSMV) resulted in a substantial reduction in the growth and spread of hyphae in Pst and weakened the virulence of Pst on wheat. Our results suggest that PstSTE12 probably acts at an intersection participating in the invasion and mating processes of Pst, and provide new insights into the comprehension of the variation of virulence in cereal rust fungi.